2005
DOI: 10.1002/chin.200549225
|View full text |Cite
|
Sign up to set email alerts
|

Magneto‐Superconductivity of Rutheno‐Cuprates

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…al [13] showed that superconductivity exists in this compound within a magnetically ordered state. Couple of substantial review articles/book chapters are also available on these ruthenocuprate magneto-superconductors [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…al [13] showed that superconductivity exists in this compound within a magnetically ordered state. Couple of substantial review articles/book chapters are also available on these ruthenocuprate magneto-superconductors [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore the possible influence of RE moment on Ru magnetic ordering in ruthenocuprate magneto-superconductors RuSr 2 GdCu 2 O 8 and RuSr 2 (Gd,Ce)Cu 2 O 10 [5,6] has increased the interest in various ruthenates containing RE. Keeping in mind the very recent report on Sr 2 RuGdO 6 [4] and our continuous interest on various rare earths containing rutheno-cuprates [7], we studied the magnetization of both magnetic RE containing Sr 2 RuGdO 6 and nonmagnetic RE based Sr 2 EuGdO 6 . Our choice of Eu and Gd guarantees the closest possible neighbors in terms of their ionic size [3].…”
Section: Introductionmentioning
confidence: 99%
“…In case of rutheno-cuprates, magneto-superconductivity was first discovered in RuSr 2 (Sm,Gd,Eu) 1.5 Ce 0.5 Cu 2 O 10 (Ru-1222) [3], and later in RuSr 2 (Gd,Eu,Sm)Cu 2 O 8 (Ru-1212) [4]. The scientific opinion is yet divided on the issue of genuine coexistence of magnetism and superconductivity in these systems [5,6]. Most of the experimental studies on the ruthenocuprates are confined to RuSr 2 Gd 1.5 Ce 0.5 Cu 2 O 10 (Gd/Ru-1222) and RuSr 2 GdCu 2 O 8 (Gd/Ru-1212).…”
Section: Introductionmentioning
confidence: 99%
“…Also to best of our knowledge the Y/Ru-1222 compounds yet reported [10,17] are all magnetic at low temperatures, but not superconducting. The situation is though different for Gd,Sm,Eu/Ru-1222 compounds which are magneto-superconducting [3,5,6,16,18].…”
mentioning
confidence: 99%